COMPARISON OF CIVIL INHERITANCE LAW AND TOBA BATAK TRADITIONAL INHERITANCE LAW REGARDING THOSE WHO ONLY HAVE DAUGHTERS AS HEIRS - Sipahutar, Gracia Taruli Apriliani; Yunanto (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
This research aims to determine the position of daughters in the distribution of inheritance based on Toba Batak customary inheritance law. This research contains a comparison of the laws contained in the Civil Code with the Toba Batak Traditional Inheritance Law that lives in society. The research method was carried out in a normative juridical manner using a comparative legal approach. This research uses primary legal sources, namely Legislation and Customary Law. Meanwhile, secondary legal sources are obtained from literature studies using journals or other written research. This literature study also uses sources obtained via the internet, such as expert opinions in webinar videos. Based on research, there are differences in provisions in the Civil Code and the Toba Batak Traditional Inheritance Law. The division of inheritance in the Civil Code equalizes the position of women and men. Meanwhile, in the Toba Batak Traditional Inheritance Law, the position of men is still considered higher than women. This research also shows that there are traditional misunderstandings that cause discrimination against women. In the more traditional Toba Batak Customary Law, women also receive inheritance, but in a different form, for example pauseang.